ON A NEW PROTEASE FROM PILEUS MEXICANUS - GAVARRON, FF; CASTANEDA AGULLO, M; BALCAZAR, MAR (INSTITUTO POLITECNICO NACIONAL, ESCUELA NACIONAL DE CIENCIAS BIOLOGICAS, CD. MEXICO, DF, MEX, 1979)
Pileus mexicanus is an arboreous plant about eight meters high, belonging to the family of the Caricaceae; it grows wild in different states of Mexico (Morelos, Guerrero, Colima, Campeche y Yucatan), and is commonly known as "cuaguayote." From fruits and
SCIENCE
Keywords: PROTEASE, PILEUS, MEXICANUS; MULTIDISCIPLINARIA; CIENCIAS CLINICAS; PATOLOGIA CLINICA